Needs Analysis for the Development of Project-Based Learning (PjBL) through an Android Application to Enhance Fiqh Learning Outcomes - Imas Masruroh; Tedi Priatna; Hapid Hapid; Tarsono Tarsono (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
This study is motivated by the low learning outcomes of Madrasah Aliyah students in Fiqh, as preliminary research shows that only 70% of tenth-grade students met the minimum competency criteria (KKM) of 75, indicating suboptimal performance. The purpose of this study is to analyze the need for the development of Project-Based Learning (PjBL) through an Android application to improve Fiqh learning outcomes at MAN 2 Bandung and MAS Baitus Shofaa Ciheulang Ciparay Bandung. The research design employs a naturalistic qualitative approach. The sampling technique used is purposive sampling, and data collection methods include interviews, observations, and documentation. Data analysis is conducted using techniques of data reduction, data presentation, and verification.Research results revealed three key findings: 1) There is a need for more engaging, tech-based learning in Fiqh education, and the "MaBar Fiqih" app could boost student interaction and critical thinking. 2) The Fiqh curriculum at both madrasas, following Kurikulum Merdeka, integrates key topics like zakat and hajj into an Android-based PjBL to enhance practical learning. 3) MAN 2 students are more tech-savvy, while MAS Baitus Shofa students are eager to learn despite lower digital literacy, making PjBL adaptable to both groups' needs for better engagement and outcomes